Analisis Swot pada Manajemen Stratejik dalam Platform Belanja Online - Annisa Karenina Ajie; Astrid Fitria Malik; Luthfia Salsabilla; Nanda Hamidah; Salsabila Putri Setiawan; Suhartini Suhartini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The digital revolution has changed the way of shopping, encouraging the growth of online shopping platforms that offer convenience for consumers. In intense market competition, SWOT analysis becomes important to help online shopping platforms identify strengths, weaknesses, opportunities and threats, and formulate strategies to maintain competitive advantages. The research aims to understand how these platforms can remain relevant and competitive in the digital era. This research uses literature studies to collect data from journals, articles and online sources, in order to analyze strengths, weaknesses, opportunities and threats in the strategic management of online shopping platforms. The results of this SWOT analysis are then used to formulate strategy recommendations that can improve the platform's operations and competitive position in the e-commerce market.